STRATEGI BISNIS YANG SUKSES: PENGARUH ENTREPRENEURIAL ORIENTATION TERHADAP MARKET ORIENTATION DAN KINERJA USAHA - Imam, Achmad; Hamzah, Moh.; Zainurrafiqi, Zainurrafiqi (Al-Amien Prenduan University, Sumenep, 2025)
This study aims to analyze the effect of entrepreneurial orientation on market orientation and its impact on business performance in micro, small, and medium enterprises (MSMEs) in Pamekasan Regency. Entrepreneurial orientation and market orientation are important factors that can affect the competitiveness and business performance of MSMEs, especially in facing competitive market dynamics. The research method used is explanatory research with data collection through questionnaires. Purposive sampling technique was used to select 400 MSME managers in Pamekasan Regency as respondents. The collected data were analyzed using PLS-SEM with WarpPLS software to test the relationship between the research variables. The results showed that entrepreneurial orientation has a significant effect on market orientation, which in turn also has a positive effect on business performance. This finding indicates that a strong entrepreneurial orientation will improve the ability of MSMEs to orient their businesses towards the market, which ultimately contributes to improving business performance. This study makes an important contribution to the development of strategic management theory, especially in the context of MSMEs, and provides recommendations for MSME actors to improve entrepreneurial orientation in order to strengthen their market orientation and business performance. These findings are also relevant for policy makers who want to encourage improved performance of MSMEs at the regional level..